Pengaruh Perubahan Kurikulum 2013 ke Kurikulum Merdeka terhadap Pembelajaran di Kelas V A SDN 101765 Bandar Setia - Aufa Aufa; Yesa Dwi Khairani; Tri Fauziah Hasana; Fitri Ana Daulay; Nurul Fadilah Nst; Azmi Oktari Harahap (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to find out the influence of the 2013 curriculum change to the independent curriculum on learning in class V A at SDN 101765 Bandar Setia. This research is a type of research that uses qualitative research methods. The data collection technique uses the interview method. This research discusses the influence of curriculum changes on the learning process, both for teachers and students. This article also discusses the challenges for teachers in teaching during the 2013 curriculum change to the independent curriculum and discusses what curriculum is more effective to use in learning. Keywords: , ,